The invaders - Waclawiak, Karolina 1979- (New York, NY Regan Arts, 2015)
Over the course of a summer in a wealthy Connecticut community, a forty-something woman and her college-age stepson's lives fall apart in a series of violent shocks. Cheryl has never been the right kind of country-club wife. She's always felt like an outsider, and now, in her mid-forties--facing the harsh realities of aging while her marriage disintegrates and her troubled stepson, Teddy, is kicked out of college--she feels cast adrift by the sparkling seaside community of Little Neck Cove, Connecticut. So when Teddy shows up at home just as a storm brewing off the coast threatens to destroy the precarious safe haven of the cove, she joins him in an epic downward spiral
1
Keywords: Middle-aged women -- Fiction; Middle-aged women; Rich people -- Fiction; Rich people; Connecticut -- Fiction; Connecticut; Fiction; Fiction